PENGEMBANGAN MEDIA PETA SEJARAH BERBASIS MACROMEDIA FLASH SEBAGAI SARANA SISWA BELAJAR MANDIRI - Kurniawan, Imam Satria; Suryani, Nunuk; Djono, D. (HISTORIKA, 2019)
Research development aims to: (1) described teaching history in senior high school district Pulau Rimau; (2) described the development of material based history of Peristiwa Front Langkan to improve people nationalism; (3) described the effectiveness of material based history the front ledge to improve people nationalism students.Research conducted is research development (Research and Development) using methods of Borg and Gall .The method includes: (1) the study introduction , namely the literature study, field studies, and findings teaching needs; (2) developmental stage covering the prototype design, validation expert, the trial one by one, and trial to more participants; (3) the step of experiment the effectiveness of covering test whether material and feasibility history.The research results show that: (1) teaching history still focused on one source the textbook without any additional or other sources a supporting, the curriculum is using KTSP curriculum, teachers have not have sufficient knowledge about the development of teaching materials; (2) The teaching materials developed with follow a procedure the development of which adapted to a syllabus, validation three experts who put a value the average score 4 for a category â€œgoodâ€;Â  trial one by one done on five students and fifteen students, the revision related the literature and grammar; the results of the tryouts broad shows differences in average between class control and class experiment where class experiment more better in terms of achievement and nasioanlisme; (3) the implementation of teaching materials history based Peristiwa Front Langkan to improve nasioanlism proven effective, proven from the acquisition value post-test on class control and experiment to aspects level of achievement with significant 0,000 < 0,025 and than nasionalism aspect with significant 0,000 < 0,025. Shows that Ho rejected which means there is a difference in positive and significant .Â